A decade of using small-to-medium throughput allele discrimination assay to determine prion protein gene (Prnp) genotypes in sheep in Slovenia. (January 2018) - Zabavnik, Jelka; Cotman, Marko; Juntes, Polona; Ambrozic, Ivan
Sheep with valine (V) at codon 136 and glutamine (Q) at codon 171 of the prion protein gene ( Prnp ) are highly susceptible to classical scrapie, whereas phenylalanine (F) at codon 141 and histidine (H) at codon 154 play a major role in the susceptibility to atypical scrapie. A TaqMan real-time PCR assay was developed to determine Prnp alleles at codons 136, 141, 154, and 171 and used in classical scrapie eradication and breeding programs adopted in Slovenia. The frequency of the most resistant genotypes ARR/ARR and ARR/ARQ increased significantly in tested animals ( n = 35, 138) from 6.7 and 27.1% of the tested sheep in 2006 to 12.1 and 32.4%, respectively, in 2015. Frequencies of more susceptible genotypes ARQ/ARQ and ARQ/VRQ decreased significantly from 36.4 and 3.5% in 2006 to 31.1 and 1.8%, respectively, in 2015. The most susceptible genotype VRQ/VRQ was detected in <0.5% of tested sheep. Frequencies of alleles AFRQ and AHQ affecting the susceptibility to atypical scrapie did not change significantly. The developed assay was suitable for genotyping on a small-to-medium throughput scale and was successfully used in classical scrapie eradication, as well as for the selection of classical scrapie–resistant sheep within breeding programs in Slovenia.